(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In this article is examined vision of founder ofGerman classic philosophy of I. Kant of culture ingeneral, thinking cultures in particular. The problems ofculture are examined I. Kant in works devotedphilosophy of history and philosophical anthropology (asphilosophical studies about a man). But although does heconsider that, in her «worldcivil value» there is a question thebasic questions of philosophe:« What man?» nevertheless headheres to world view Naturecenter, declared thatabout itself beginning of New time. From here, to investigatea man, societies and history maybe only on the basis ofresearch of Nature. Man as creation of nature, on I. Kant inwardly аntitezis. Hehas propensity the commonunication with to itself similarat the same time strong aspiring to solitude, i.e. propensity tounsociability. I. Kant distinguishes general and private culturesheartfelt to ability. The culture of the cognizing thinking consists in that, strictly follow the rules of reason. Key words: Kant, logic, thinking culture, transcendental logic, transcendental analytic, transcendental dialectics, philosophy.